Ecologia do acará-disco (Symphysodon aequifasciatus, Pelegrin, 1904) (Perciformes: Cichlidae) em igarapés no lago Amanã, Amazonas, Brasil - Hercos, Alexandre Pucci (Instituto Nacional de Pesquisas da Amazônia - INPA, 2014)
Ornamental fishing has become an important economic activity for Amazonas state, withgreen discus Symphysodon aequifasciatus (Pelegrin, 1904) being one of the most important species in the ornamental fish trade in the state, and also the main species traded in the middle Solimões region. Despite its economic importance, little is known about its biological and ecological characteristics. Autoecology studies the relationships of a single species within its environment, essentially defining the limits of tolerance and preference of the species in face of several ecological factors, examining the action of the environment on its morphology, biology, physiology and behavior. Biological and ecological parameters of the main exploited species are poorly known, nevertheless, these studies are fundamental for a better understanding of relationships between fishes and their natural environments, creating subsidies for sustainable management plans for these species. The present study aimed to investigate aspects of the S. aequifasciatus autoecology at Amana Sustainable Development Reserve, in Amazonas state, Brazil. The following aspects were studied: the species diet, evaluating the items consumed and its temporal variation, the trophic category occupied by the species, its growth rate and longevity. The species reproductive biology was also studied by checking its population structure, estimating the average size of first maturation, investigating its breeding season and determining its spawning type. Additionally, the S. aequifasciatus genetic populations structure was analyzed within streams associated with Amana Lake, identifying different populations and characterizing potential geographic barriers to gene flow. In addition, a revision of the management norms described in the ornamental fishes Management Plan for the study area was carried out. Genetic analyzes failed to separate (sub) populations of green discus along Amanã Lake, indicating that the study area is a single large panmictic population. Both animal and plant origin items were identified within the species diet, classified as omnivore. The feeding temporal variation observed to the species shows its ability to adapt its diet under changes on food items availability.The species has a long life cycle and intermediate growth rates typical of species with an "equilibrium" life strategy. It reaches sexual maturity in its first year of life measuring around eleven centimeters long, the maximum longevity recorded was of more than eight years and the males are larger than the females. Spawning occurs at the end of the flooding season and it takes place probably in the flooded forest. The species spawns only once during a single hydrological cycle, when approximately 1000 oocytes are liberated. Characteristics of S. aequifasciatus populations life cycle at Amanã Lake indicate a tendency to classify it as a K-strategist species. Once it is a single population, all streams studied (10) can become potential areas for collection of green discus, nevertheless, a previous survey will be necessary in order to calculate the abundances of the species in each of these igarapés. As captivity does not cause green discus mortality neither changes animals‟ health conditions, it is recommended to choose fish catching and selling period according to commercial issues. Although, a breeding peak was identified between April and June, what makes the months of September and October proper for managed collection period. Observing S. aequifasciatus`s sexual maturation point it is suggested that the minimum catch size for managed fishery at Amanã Lake is 11.50 centimeters. The present study generated important information about S. aequifasciatus ecology which can be very useful to improve the management plan elaborated for the species at the Amanã Sustainable Development Reserve.
Keywords: Acará-disco; Symphysodon aequifasciatus; Pesca ornamental